Constructive basis for the development of the extreme zones of Siberia and the Russian arctic - Sarvut, Tat'yana (International Journal of Engineering and Technology, 2018)
The paper describes the constructive basis for building and structure designing in the difficult regions of Siberia and the Russian Arctic and development of a new approach to the design of buildings and structures in the Russian Arctic in the face of climate change. Severe climate and weather conditions of the northwestern territories of Russia are rapidly changing due to the global warming. The structural changes in development and construction, following this irreversible process, are highlighted and discussed in relation to the foundations and constructive systems. The paper provides an overview of methods and technological approaches to the extreme zone construction. The application of modern methods of design and construction with the involvement of competent "practitioners" increases the pace of construction and reduces its cost; Architectural and constructive solutions should focus on the developing areas of business and tourism. We suggest the possible protective measures against the transgression of the World Ocean and thawing of the permafrost. The term â€œspecial Arctic basesâ€, denoting the new type of settlements in the Russian Arctic, is introduced. The introduction of constructive solutions and the development of planning solutions for the bases will help to ensure a stable activity in the region.Â Â